Deliberate self-harm is associated with allelic variation in the tryptophan hydroxylase gene (TPH A779C), but not with polymorphisms in five other serotonergic genes. - Pooley, E; Houston, K; Hawton, K; Harrison, P (2003)
BACKGROUND: There is a heritable component to suicidal behaviour, encouraging the search for the associated risk alleles. Given the putative role of the 5-HT (5-hydroxytryptamine; serotonin) system in suicidal behaviour, serotonergic genes are leading candidates. In particular, several studies have reported an association with variants in the tryptophan hydroxylase (TPH) gene. METHOD: We studied six serotonergic gene polymorphisms in a well-characterized sample of 129 deliberate self-harm subjects and 329 comparison subjects. The polymorphisms were TPH (A779C), 5-HT transporter (5-HTT, LPR S/L), monoamine oxidase A (MAOA G941T), 5-HT1B receptor (HTR1B G861C), 5-HT2A receptor (HTR2A T102C), and 5-HT2C receptor (HTR2C Cys23Ser). Genotyping was done using polymerase chain reaction (PCR)-based assays. The primary analyses compared allele and genotype frequencies between cases and controls. There were a limited number of planned secondary analyses within the deliberate self-harm group. RESULTS: The TPH A779 allele was more common in deliberate self-harm subjects than in controls (OR 1.38, 95% CI 1.02-1.88; P = 0.03). None of the other polymorphisms was associated with deliberate self-harm. Within the deliberate self-harm group there were no associations with impulsivity, suicide risk, lifetime history of depression, or family history of deliberate self-harm. CONCLUSIONS: Our data extend the evidence that allelic variation in the TPH gene is a risk factor for deliberate self-harm. No evidence was found to implicate the other polymorphisms.